2020
DOI: 10.1261/rna.076042.120
|View full text |Cite
|
Sign up to set email alerts
|

Pseudouridine-mediated stop codon readthrough in S. cerevisiae is sequence context–independent

Abstract: We have previously shown that when the uridine of a stop codon (UAA, UAG, or UGA) is pseudouridylated, the ribosome reads through the modified stop codon. However, it is not clear as to whether or not the pseudouridine (Ψ)-mediated readthrough is dependent on the sequence context of mRNA. Here, we use several different approaches and the yeast system to address this question. We show that when a stop codon (premature termination codon, PTC) is introduced into the coding region of a reporter mRNA at several dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…(c) Polyadenylation sites annotated by the Poly(A)Site 2.0 atlas35 . GM12878 specific data from: (d) PolII ChiP-seq sites47 ; (e) CAGE sites for the positive strand48 ; (f) Three replicate DNase-HS tracks49 . (g) Read coverage from full-length nanopore 5′ RACE sequencing.…”
mentioning
confidence: 99%
“…(c) Polyadenylation sites annotated by the Poly(A)Site 2.0 atlas35 . GM12878 specific data from: (d) PolII ChiP-seq sites47 ; (e) CAGE sites for the positive strand48 ; (f) Three replicate DNase-HS tracks49 . (g) Read coverage from full-length nanopore 5′ RACE sequencing.…”
mentioning
confidence: 99%
“…Base miscalls relative to canonical training data in our ADGRE1 aligned reads ( Fig. 8g) strongly suggest an unannotated pseudouridine in the stop codon, which is known to cause translation read through 37 . Importantly, this miscall was absent from in vitro transcribed nanopore direct RNA sequence data [11][12][13]15 .…”
Section: A Dhesion G Protein-coupled Receptor E1 ( Adgre1)mentioning
confidence: 93%
“…The * (red background) is the canonical stop codon for ADGRE1. A pseudouridine at the first nucleotide of that stop codon can promote ribosome read through in other genes 37 . ( b ) High confidence mRNA scaffolds aligned to the unannotated isoform.…”
Section: Adaptation Ofmentioning
confidence: 99%
“…The authors were also able to identify the amino acids incorporated at the pseudouridylated PTC codons: primarily tyrosine and phenylalanine at ΨGA codons and serine and threonine at ΨAA and ΨAG codons. The Yu lab recently showed that the readthrough effect promoted by pseudouridylation of PTCs is independent of the target sequence, suggesting that this technology is theoretically applicable to all nonsense mutations [ 202 ]. Importantly, it appears that a single U-to-Ψ conversion at the PTC not only promotes PTC-readthrough during translation but also suppresses NMD.…”
Section: Therapeutic Potential Of Rna Modificationsmentioning
confidence: 99%